Translated "Handbook of COVID-19 Prevention" - Ruzaik, Fareena (Neptune Publication (Pvt.) limited, 320. Pahalawela Road, Pelawatta, Battaramulla, Sri Lanka, 2020)
A book on “Handbook of COVID-19 Prevention” translated from English to Tamil language and published by the Neptune Publication (Pvt.) limited, 320. Pahalawela Road, Pelawatta, Battaramulla, Sri Lanka, 2020.
English to Tamil Translation
A book on “Handbook of COVID-19 Prevention” translated from English to Tamil language and published by the Neptune Publication (Pvt.) limited, 320. Pahalawela Road, Pelawatta, Battaramulla, Sri Lanka, 2020
Keywords: Covid-19, guidelines, awareness